FODMAP ve Bazı Hastalıklarda FODMAP Diyet Uygulamaları - GÜNEŞ BAYIR, AYŞE; Semiz D.; Güneş Bayır A. (Özgür Yayınları, 2024)
Short-chain carbohydrates, called FODMAPs, are fermentable, oligosaccharides, disaccharides, monosaccharides and polyols and are found in most foods. Some individuals may experience gastrointestinal symptoms such as gas, diarrhea, abdominal bloating and cramping when consuming foods containing FODMAPs. In addition, this significantly reduces the quality of life of these individuals and a low FODMAP diet is offered to control these symptoms. The Low FODMAP diet is based on restricting the intake of highly osmotic short-chain carbohydrates that are not slowly absorbed or digested in the human small intestine. On the other hand, Low FODMAP diet planning is implemented in three phases: FODMAP restriction, FODMAP reintroduction and then individualized selective FODMAP according to patients\" tolerance. The Low FODMAP diet has been applied in other functional gastrointestinal disorders, such as irritable bowel syndrome, non-celiac gluten sensitivity, inflammatory bowel diseases, and other functional gastrointestinal disorders. Thus, there is a reduction in symptoms and an increase in the quality of life of individuals with these conditions. However, FODMAP restriction in the diet of individuals also has disadvantages. Since most of the FODMAP components are prebiotic, it may lead to a decrease in fiber intake in the diet and may have negative effects on the intestinal microbiota. A health professional should be involved in the implementation of a low FODMAP diet and follow-up of symptoms. In particular, dietitians should determine the FODMAP components to which the patient is exposed on a daily basis, test food tolerance, check for dietary dependence, provide patient-specific dietary instructions, and ensure maximum dietary diversity by offering alternatives to food sources. This review aims to examine FODMAP carbohydrates, explain the low FODMAP diet, and provide an update on the evidence for the effects of a low FODMAP diet.
Keywords: Veteriner Bilimleri; Besin Hijyeni ve Teknolojisi; Tarımsal Bilimler; Sağlık Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Veterinary Sciences; Food Hygiene and Technology; Agricultural Sciences; Health Sciences; Natural Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bitki ve Hayvan Bilimleri; Doğa Bilimleri Genel; VETERİNERLİK BİLİMLERİ; ÇOK DİSİPLİNLİ BİLİMLER; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Natural Sciences (SCI); PLANT & ANIMAL SCIENCE; NATURAL SCIENCES, GENERAL; VETERINARY SCIENCES; MULTIDISCIPLINARY SCIENCES; At; Veterinerlik (çeşitli); Genel Veterinerlik; Multidisipliner; Equine; Veterinary (miscellaneous); General Veterinary; Multidisciplinary